2022
DOI: 10.3390/ijms23147663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymeric Nanoparticles with Entrapped Fish Oil or Mupirocin on Skin Wound Healing Using a Porcine Model

Abstract: The utilization of poly(lactic-co-glycolic) acid (PLGA) nanoparticles (NPs) with entrapped fish oil (FO) loaded in collagen-based scaffolds for cutaneous wound healing using a porcine model is unique for the present study. Full-depth cutaneous excisions (5 × 5 cm) on the pig dorsa were treated with pure collagen scaffold (control, C), empty PLGA NPs (NP), FO, mupirocin (MUP), PLGA NPs with entrapped FO (NP/FO) and PLGA NPs with entrapped MUP (NP/MUP). The following markers were evaluated on days 0, 3, 7, 14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Concurrently, an intricate network of biological molecules such as growth factors and cytokines orchestrates this multifaceted process. The intricate orchestration of wound repair is governed by intercellular interactions characterized by dynamic and precise crosstalk among various signaling pathways [1,8–10] . Broadly, wound healing includes four sequential yet overlapping stages: hemostasis, inflammatory responses, proliferation, and tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, an intricate network of biological molecules such as growth factors and cytokines orchestrates this multifaceted process. The intricate orchestration of wound repair is governed by intercellular interactions characterized by dynamic and precise crosstalk among various signaling pathways [1,8–10] . Broadly, wound healing includes four sequential yet overlapping stages: hemostasis, inflammatory responses, proliferation, and tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids have been shown to be essential in skin tissue reconstruction processes [32]. Animal studies have demonstrated the beneficial effect of the fatty acids present in cod liver oil on the prevention or healing of skin wounds, both topically and internally (orally as a supplement or by injection) [33][34][35][36][37][38][39][40][41][42]. Fish liver oil stimulates angiogenesis, thus promoting wound healing.…”
Section: Introductionmentioning
confidence: 99%